Sistem Informasi Prevalensi HIV di Wilayah Kota Surakarta - Nicko Ilham Akbar; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2025)
he spread of HIV remains a significant public health issue globally, including in Indonesia. This study focuses on mapping the prevalence of HIV in the districts of Solo City from 2021 to 2023 using Geographic Information System (GIS) technology. Employing QGIS software, spatial analysis was conducted to create thematic maps showcasing the annual distribution of HIV prevalence across districts. The findings reveal a consistent increase in HIV prevalence over the three years, with Banjarsari and Jebres districts recording the highest rates. This spatial distribution correlates strongly with population density and urbanization levels. The study emphasizes the importance of targeted interventions, including regular health screenings, education programs, and equitable healthcare access to curb the spread of HIV in high-risk areas. The results serve as a scientific foundation for policymakers to enhance HIV prevention and management strategies.